2011
DOI: 10.1007/s00477-011-0481-9
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic of vegetation coverage and its response to climate factors in Inner Mongolia, China

Abstract: Normalized Difference Vegetation Index (NDVI) is widely recognized as a good indicator of vegetation productivity. Diagnosing the NDVI trend and understanding climatic factors influences on NDVI can predict the productivity changes under different climatic scenarios. This paper examined NDVI dynamic and its response to climate factors during a 10 year period (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) in Inner Mongolia. The main findings are as follows: (1) The NDVI multi-scale character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
5
33
0
1
Order By: Relevance
“…They delineated that the NDVI and rainfall relation is significant and NDVI maintained the 3 ~ 4 years periodicity which is associated with rainfall. Also, it is reported that the wavelet analysis is a very useful technique in order to investigate the impact of climate factors on NDVI with most suitable time scale (Yang et al, 2012). In the present study also, we used NDVI and API which is a by-product of rainfall to understand the periodicities associated with them.…”
Section: Monsoon Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…They delineated that the NDVI and rainfall relation is significant and NDVI maintained the 3 ~ 4 years periodicity which is associated with rainfall. Also, it is reported that the wavelet analysis is a very useful technique in order to investigate the impact of climate factors on NDVI with most suitable time scale (Yang et al, 2012). In the present study also, we used NDVI and API which is a by-product of rainfall to understand the periodicities associated with them.…”
Section: Monsoon Activitymentioning
confidence: 99%
“…This wavelet analysis can also be applied to geophysical variables (Foufoula-Georgiou and Kumar, 1995) and the theoretical treatment of wavelet analysis is reported by Daubechies (1992). Studying NDVI variation with respect to the rainfall changes have been carried out by many people (Lark and Webster, 1999;He et al, 2012;Yang et al, 2012). He et al (2012) used 10 day composite AVHRR NDVI data from 1985 to 2007 and examined the seasonal and inter-annual relationships with rainfall by applying the wavelet spectral analysis over Canadian Ecosystems.…”
Section: Monsoon Activitymentioning
confidence: 99%
“…The relationship between NDVI and temperature or precipitation based on meteorological stations was mainly done in Excel 2013 and ArcGIS 10.2 software. The formula of correlation coefficient is as follows [23]:…”
Section: Correlation Analysismentioning
confidence: 99%
“…Globally, the NDVI in much of the surface of the land indicated great changes from 1982 to 2012, and about half of the change displayed seasonal dynamics [23]. For example, the Annual NDVI had a slightly increasing trend in Central Asia from 1982 to 2012 [24].…”
Section: Introductionmentioning
confidence: 99%
“…En particular, el NDVI (Normalized Difference Vegetation Index) es uno de los más utilizados ya que es un estimador lineal de la radiación fotosintéticamente activa interceptada por la vegetación y su mapeo permite describir los patrones regionales de productividad primaria neta y los diferentes atributos del comportamiento fenológico a partir de la curva anual de crecimiento (ALCARAZ-SEGURA et al, 2009;JÖNSSON, 2009;EKLUNDH, 2002EKLUNDH, , 2004GANDINI, 2013b;PARUELO et al, 1997;PARUELO et al, 2001;VÁZQUEZ et al, 2013). De esta manera, el NDVI se ha empleado en la caracterización de unidades funcionales de ecosistemas (ATZBERGER; EILERS, 2011;GANDINI et al, 2012;IVITS et al, 2013;GANDINI, 2013b;PARUELO et al, 2001), en el mapeo de la heterogeneidad de paisajes (ALI et al, 2013;BARRAZA et al, 2013) y su relación con variables climáticas (MELENDEZ-PASTOR et al, 2010;VAN LEEUWEN et al, 2013;YANG et al, 2012).…”
Section: Introductionunclassified